2008
DOI: 10.1007/s00402-007-0554-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum cardiac troponin I in older patients with hip fracture: incidence and prognostic significance

Abstract: Peri-operative myocardial injury is common in older HF patients but is frequently unrecognised clinically. Elevated blood cTnI level is an independent predictor of prolonged length of hospital stay (>or=20 days), need for long-term RCF and mortality (if cTnI >or=1 microg/l).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 28 publications
4
34
0
Order By: Relevance
“…The present study is the largest series of subjects undergoing major orthopedic surgery with troponin measurements and long-term follow-up. Our data support the findings of small orthopedic surgery studies, 914,19,20 and augment the short-term results of large prospective registries of subjects undergoing non-cardiac surgery. 15,16 In the large, prospective Vascular Events in Non-Cardiac Surgery Subjects Cohort Evaluation (VISION) study, elevated perioperative troponin elevations correlated with 30-day mortality.…”
Section: Discussionsupporting
confidence: 86%
“…The present study is the largest series of subjects undergoing major orthopedic surgery with troponin measurements and long-term follow-up. Our data support the findings of small orthopedic surgery studies, 914,19,20 and augment the short-term results of large prospective registries of subjects undergoing non-cardiac surgery. 15,16 In the large, prospective Vascular Events in Non-Cardiac Surgery Subjects Cohort Evaluation (VISION) study, elevated perioperative troponin elevations correlated with 30-day mortality.…”
Section: Discussionsupporting
confidence: 86%
“…Our study showed an overall incidence of myocardial necrosis and major bleeding of 5.8% and 5.4%, respectively. Previous studies have shown an incidence of perioperative myocardial necrosis ranging from 1% to 53% 39 , depending on the study population. For example, Chong et al found an incidence of perioperative myocardial necrosis of 53% in subjects with a mean age of 79 years undergoing emergency orthopedic surgery 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Perioperative thrombotic complications are a major cause of morbidity and mortality, occurring in 1–53% of cases depending on type of surgery, comorbidities present, and outcome ascertainment 19 . On the opposite end of the haemostatic equilibrium, major perioperative bleeding increases the risk of reoperation, overall length of stay, and hospital costs 10 .…”
mentioning
confidence: 99%
“…11,19Y22 Earlier studies on myocardial injury related to hip fracture have been relatively small and most of them focus on elderly or patients with high cardiac risk. 6,11,20,21 To date, no comprehensive analysis of perioperative myocardial infarctions in hip fracture patients has been performed, and none of the earlier studies have used serial ECG recordings to assess myocardial ischemia or infarction. The purpose of this prospective study was to determine the incidence of myocardial infarctions in an unselected population of patients with acute hip fracture and to assess the characteristics and risk factors of perioperative myocardial infarctions in this fragile patient group.…”
Section: Introductionmentioning
confidence: 99%